A toolkit for bioimaging using near-infrared AgInS2/ZnS quantum dots. Issue 41 (21st September 2015) - Shamirian, Armen; Appelbe, Oliver; Zhang, Qingbei; Ganesh, Balaji; Kron, Stephen J.; Snee, Preston T.
Abstract : Cadmium free near-infrared AgInS2 /ZnS quantum dots have been synthesized and used for imaging the microenvironment of cancer tumours. Abstract : Presented are a set of procedures to produce water-soluble AgInS2 /ZnS near-infrared emitting quantum dots for use as biological imaging agents. The known difficulty of producing near-infrared core/shell materials is resolved by overcoating the AgInS2 cores at a low temperature using highly reactive precursors. Several methods are explored to impart water solubility of the hydrophobic as-prepared materials. Insofar as achieving aqueous dispersion of quantum dots has only limited biological utility, several methods to further functionalize them are examined. In vivo studies are conducted using these quantum dots to demonstrate the ability to model delivery of nanoparticles to the tumour microenvironment.